(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
Introduction: The aim of this study was to evaluate the neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV) in patients with recurrent aphthous stomatitis (RAS). Materials and Methods: Forty patients who were diagnosed with RAS between May 2018 and January 2019 were included in this study. Forty age- and gender-matched healthy subjects were also enrolled as a control group. Neutrophil, lymphocyte, and platelet counts were compared between groups, in addition to NLR, and MPV values. Results: NLR were significantly higher in patients with RAS compared with the control group (P<0.05). while MPV were not significantly different between both groups. Conclusion: The present study revealed an increased NLR among RAS patients compared with healthy controls. This suggests that development of RAS involves an inflammatory process. We believe that NLR could be used as a cheap and simple marker of inflammation. المقدمة: تهدف هذه الدراسة لتقييم نسبة العدلات إلى اللمفاويات NLR وحجم الصفيحات الكلي MPV. المواد والطرائق: تم فحص أربعين مريضاً لديهم التهاب فم قلاعي ناكس بين ايار 2018 و كانون الثاني 2019 يمثلون مجموعة الدراسة وأربعين شخصا مترابطين بالعمر والجنس يمثلون المجموعة الشاهدة. تم مقارنة قيم العدلات واللمفاويات والصفيحات الدموية بالإضافة إلى نسبة العدلات إلى اللمفاويات NLR وحجم الصفيحات الكلي MPV. النتائج: كانت نسبة العدلات إلى اللمفاويات NLR أعلى لدى مرضى التهاب الفم القلاعي الناكس. في حين أن حجم الصفيحات الكلي MPV كان بدون أي دلالة ذات أهمية إحصائيا. المناقشة: تعكس الدراسة الحالية ارتفاع نسبة العدلات إلى اللمفاويات NLR لدى مرضى التهاب الفم القلاعي الناكس مقارنة بالمجموعة الشاهدة. بالتالي يمكننا الاستنتاج بأن المرض يطور عملية التهابية. يمكننا القول أن NLR علامة تشخيصية سهلة وفعالة لهؤلاء المرضى.